Lietuviškų knygų tiražai 1795-1864 metais - Navickienė, Aušra (Knygotyra, 1996)
Editions of printings are a very important indicator of publishing activity, which characterizes quantitatively this publishing activity itself and shows the cultural and educational condition in the period which is treated.There is not enough information about editions of books in the nineteenth century. There are 58 Lithuanian printing editions, which have been discovered by using various sources and special calculations. This new data expands the information presented in the Lithuanian national retrospective bibliography.Information about all editions of Lithuanian books during 1795-1864, which is known now, is presented in the table. The data of this table also forms the basis of speculations about the dynamics and factors of editions.Editions of Lithuanian printings increased significantly during 1795-1864. At the end of the 18th century, the general annual printings edition was 3,000 copies. In the mid-nineteenth century, this number increased to 50,000-70,000 copies. Even editions of ABC books increased from 1,500 to 5,000 copies.The different sizes of editions of books on various subjects were determined by their content, purpose, and the different financial capacities of publishers. Printings for educational, informational, and administrative purposes had larger editions: calendars (almanacs) - from 3,000 to 10,000 copies, legal documents - from 3,000 to 5,000, and proclamations up to 10,000 copies.Editions of fiction fluctuated from 500 to 5,000 copies, and those printings intended to inform about the trade of books were made up of only a few hundred copies.We can also speak about the mass spreading of catechisms, books promoting religious morality, ceremony books, prayer books, and songbooks throughout the entire period in question. Their average editions in the mid-century were: catechism - 1,500-5,000, moral preachings - 4,000-15,000, ceremony books - 10,000, prayer books - 3,000-10,000, and religious songbooks - 5,000 copies.Books intended only for priests, which were used for pastoral care, organizational, and administrative means of the church, had smaller editions - 300-500 copies.Increased editions of Lithuanian books made the Lithuanian press cheaper and more accessible to readers. On the other hand, readers not only increased in number, but their reading demands expressed substantive changes too. These changes show the tendencies of secularization and democratization processes in the culture.